Physical and emotional impacts on the health care of informal caregivers of patients with Alzheimer’s disease (Research, Society and Development, 2021)
Alzheimer’s disease significantly affects the daily activities of the patient and the people responsible for his/her care. Thus, given the great physical and emotional wear of caregivers, the objective of this study was to analyze how the care provided to patients with Alzheimer’s can physically and emotionally impact caregivers. This is an integrative literature review, using the Scielo and PubMED databases, and the descriptors “physical impacts”, “emotional impacts”, “caregivers”, “Alzheimer’s disease” and “family members”, in different combinations. Articles published between 2010 and 2020, in English, Spanish, Portuguese and French were included. It was observed that most caregivers of demented patients are women, in general, family members of the patient. In addition, with de progress of the disease, the physical and emotional exhaustion of caregivers tends to increase, causing exacerbated stress, the onset of chronic diseases, anxiety, abdications of pleasurable activities for the caregiver, depression and feelings of loneliness and abandonment. Thus, it was seen that the care process of patients with Alzheimer’s is quite complex, especially in the more advanced stages of the disease, causing abdications od the caregiver’s wishes and negative physical and emotional impacts on their health and quality of life.